243 Oral hydration therapy affects health, and performance in high-risk, newly received beef calves. - Tomczak, D (J Anim Sci, 2018)
The study objective was to evaluate the health and performance impacts of oral hydration therapy during initial processing of high-risk calves during a 56-day receiving period. In experiment 1 (EXP1), 6 truckload blocks of crossbred heifers (n=664, initial BW = 197.1 ± 5.8 kg) were randomized to 1 of 2 treatment pens (n=6/treatment; 55 ± 3 animals/pen) by truck exit order before initial processing. In experiment 2 (EXP2), 3 truckload blocks of crossbred bull (n=242) and steer (n=55) calves (initial BW=188.9 ± 19.1 kg) were stratified by sex and purchase BW and randomly assigned to 1 of 2 treatment pens (n=15/treatment; 10 animals/pen) upon initial processing. At arrival, calves received 0.57 L water/45.4 kg BW from a modified oral drenching apparatus (H2O) or no water administration (CON) according to treatment pen assignment. Standard arrival processing procedures were implemented and bulls were surgically castrated and administered meloxicam in EXP2. Treatment-blinded technicians evaluated calves daily and assigned a clinical illness score (CIS) for bovine respiratory disease (BRD). Cattle qualifying for BRD treatment (EXP1: CIS ≥2; EXP2: CIS ≥2 and rectal temperature ≥40°C) were administered an antimicrobial. In EXP1, BW, ADG and G:F did not differ (P≥0.63); however, H2O numerically increased DMI (5.29 vs. 5.09 kg/day; P=0.12) and tended to increase BRD morbidity (29.0 vs. 21.5%; P=0.07). There was no difference (P≥0.39) in second or third BRD morbidity rate or mortality rate. In EXP2, final BW (256.8 vs. 248.7 kg) and overall ADG (1.19 vs. 1.07 kg/day) tended to increase (P=0.08) and DMI for day 42 to 56 (7.54 vs. 6.85 kg/day) was greater (P<0.01) for H2O vs. CON. However, BRD-associated mortality was greater (P=0.05) in H2O (8.1%) vs. CON (2.7%). Increased performance and DMI was observed for H2O; but, health outcomes were not improved.